Comparing GDP in Constant and in Chained Prices: Some New Results - Jesus C. Dumagan (Philippine Institute for Development Studies (PIDS), 2009)
This paper's framework for GDP in chained prices yields GDP in constant prices as a special case of constant relative prices, i.e., these GDP measures differ only when relative prices change. The framework has a novel additive procedure, counter to the prevailing view that GDP in chained prices is non-additive. This procedure allows relative prices to change but when they are constant, components in chained and in constant prices are equal, implying consistency with the additivity of GDP in constant prices. Finally, GDP conversion from constant to chained prices removes the fixed base - by making the immediately preceding period the base, i.e., continuous updating - and allows relative prices to change and, thus, removes the base-period dependence and substitution bias of GDP in constant prices.
Keywords: C43; 330; real GDP; constant prices; chained prices; Fisher index; additivity